THE INFLUENCE OF THE MARKETING MIX ON THE LENDING STRATEGY OF THE COMMERCIAL & CORPORATE SEGMENT AT PT BANK ABC - Intan, Seli Venny; Nazaruddin, Nazaruddin; Wibowo, Rulianda Purnomo (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
This study aims to determine the effect of the Marketing Mix on the Commercial & Corporate Segment Credit Strategy at PT Bank ABC. The results showed that the price, product and process variables partially influenced the decision to take credit at PT Bank ABC. Place, promotion, people and physical environment variables partially have no effect on the decision to take credit at PT Bank ABC. All independent variables Product, Price, Place, Promotion, People, Process and Physical Environment simultaneously influence the decision to take credit at PT Bank ABC. In terms of price variables that affect the debtor's decision to take credit at Bank ABC, Banks can carry out appropriate pricing strategies to be charged to debtors after going through various considerations by the Bank. In terms of product variables that affect the debtor's decision to take credit at Bank ABC, the Bank can develop new credit products according to current market needs and always conduct regular product development and evaluation so that it can stay abreast of business developments in the market. In terms of process variables that affect the debtor's decision to take credit at Bank ABC, the Bank can carry out strategies from the debtor's side and the bank's internal side.